Probing CAKE-Learn English Application toward Students’ Motivation in Learning English Vocabulary at SMPN 2 Kediri - Tawali Tawali; Kamarudin Kamarudin (JUPE : Jurnal Pendidikan Mandala, 2022)
The purpose of this study was to determine whether the CAKE-Learn English Application increases students' motivation to learn English vocabulary. This study was conducted as part of the Classroom Action Research project (CAR). The information was gathered quantitatively as well as qualitatively. The researcher's instrument included a multiple choice post-test and a questionnaire non-test. The results demonstrated that the CAKE-Learn English Application could help students improve their vocabulary. The results of the first cycle show an improvement, with 16 out of 31 students, or 51.62 percent, experiencing an increase in vocabulary. The results of Cycle II revealed those 26 out of 31 students, or 83.87 percent, improved their vocabulary, and the questionnaire revealed that 87.09 percent of students increased their motivation to learn English vocabulary. As a result, the CAKE-Learn English Application was able to increase students' motivation to learn English vocabulary. Students can collaborate in groups and assist one another through the use of this media.